IMPLEMENTASI STRATEGI KEPALA SEKOLAH DALAM MEWUJUDKAN LINGKUNGAN BELAJAR ADAPTIF BAGI SISWA TUNAGRAHITA DI SLB NEGERI 1 KARAWANG BARAT - Zahra Aulia Syahzabilla; Hinggil Permana; Chairil Fajar Hadiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how the principal of SLB Negeri 1 Karawang Barat implements strategies to create an adaptive learning environment for students with intellectual disabilities, viewed from four aspects: planning, implementation, evaluation, and the supporting and inhibiting factors. The focus is directed at the implementation stage, in which formulated policies are translated into concrete actions through the placement of teachers according to expertise, curriculum adjustment, teacher competency development, and school-parent collaboration. A descriptive qualitative approach with a case-study design was used. Data were collected through observation, in-depth interviews with the principal, the vice-principal for curriculum, teachers, and parents, and documentation, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing/verification. The results show that strategy formulation was carried out through participatory vision and mission setting and a needs assessment of students. Implementation was carried out through placing teachers according to their field of expertise, applying an adaptive curriculum through Individual Learning Programs, and developing teacher competence through In-House Training and learning communities. Evaluation was carried out periodically through teacher performance appraisal, academic supervision, and monitoring of student development. Supporting factors include principal leadership, teacher competence, and parental support, while inhibiting factors include limited facilities, the diverse characteristics of students, and limited teacher time for individualized services. The study concludes that the principal's strategy has been implemented systematically in accordance with the stages of strategic management, although continuous improvement of facilities and technology-based learning innovation is still required.